SPECIES DIVERSITY OF BIRDS IN CLUNGUP MANGROVE CONSERVATION SENDANG BIRU, KABUPATEN MALANG, EAST JAVA AS BIOINDICATOR - Aditya Rachmaputra; Bagyo Yanuwiadi; Amin Setyo Leksono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2018)
Clungup Mangrove Conservation (CMC) is a location managed by Bhakti Alam Sendang Biru Organization. Mangrove management activities were carried out continuously starting from mangroves clearing in 1998 until it is all used up and started replanting when people found it difficult to catch fish. Mangroves are plants which lived at maximum subsiding tide point to maximum rising tide point area, with mud as its substrate. For other organisms, mangroves used as shelter and foraging place. One of those organisms is birds, birds can be used as bioindicators of environmental quality because it has a sensitivity to environmental changes. This study divided into 4 stations based on mangrove vegetation, the results observed were for Shannon Index at 1.99-2.3 and Margalef Index at 3.5-3.8 for morning observations. While for afternoon observation resulted as Shannon Index at 1.2-2.2 and Margalef Index at 1.8-3.9. The main focus is some water birds such as Ardeola speciousa, Todiramphus chloris, Aldeco coerulescens, Butorides Striata, Todiramphus sanctus and Charadrius javanicus which shows that mangrove ecosystems provide a function of nursery ground for fish and feeding ground for birds.